Simple and Fast Approach for Synthesis of Reduced Graphene Oxide-MoS(2 )Hybrids for Room Temperature Gas Detection - Kumar, Rajesh [UNESP]; Dias, Wagner [UNESP]; Rubira, Rafael J. G. [UNESP]; Alaferdov, Andrei V.; Vaz, Alfredo R.; Singh, Rajesh K.; Teixeira, Silvio R. [UNESP]; Constantino, Carlos J. L. [UNESP]; Moshkalev, Stanislav A. (Ieee-inst Electrical Electronics Engineers Inc, 2018)
The combination of two highly versatile materials as reduced graphene oxide (rGO) and molybdenum disulfide (MoS2) forms the layered rGO-MoS2 hybrids that have great potential for sensing applications. In this paper, we developed a cost-effective, time-saving, and efficient microwave-assisted method to exfoliate rGO and MoS2 nanosheets in a powder mixture for the formation of rGO-MoS2 hybrids. The formation of hybrids with a combination of organic and inorganic 2-D layered materials offers new possibilities for the development of gas sensitive materials. The applied microwave treatment is a simple and fast process for the large-scale synthesis of rGO-MoS2 hybrids. The synthesized rGO-MoS2 hybrids were characterized by X-ray diffraction, scanning electron microscope, energy dispersive X-ray spectroscopy, Raman, X-ray photoelectron spectroscopy, and thermogravimetric analyses to determine the phase structure, surface morphology, defect formation, binding energy, thermal stability and so on. The synthesized rGO-MoS2 hybrids were tested for sensing application and showed the good performance to detect gases such as O-2, N-2, and NH3 at room temperature.
Keywords: 2-D layered materials; characterization; gas sensor; hybrids; microwave exfoliation; molybdenum disulfide (MoS2); reduced graphene oxide (rGO)